ASEAN ECONOMIC INTEGRATION AND SKILL DIFFERENTIALS IN THE INDONESIAN LABOUR MARKET - Tri Mulyaningsih (Journal of Applied Economics in Developing Countries, 2018)
This study concerns with labour market in Indonesia, an labour-abundant country, considering the impact of trade liberalization on inequalities. It focuses on the transmission of ASEAN intra-trade on inequalities through the changing of the relative price of skilled and unskilled labour. This study relies on manufacturing survey data collecting information of more than 24 thousand firms classified under 13 sectors of Harmonized System (HS). The estimation shows that international trade has contribution on wage differentials in the Indonesian labour market. Lower tariffs are associated with widen wage differentials between skilled and unskilled workers in the Indonesian manufacturing industries.Keywords: Trade Liberalization, Labor Market, Skill Inequalities, Indonesia